Chaos suppression instigated by a hyperbolic sine nonlinearity in the Chen system - Rech P.C.* (2021)
© 2021 World Scientific Publishing Company.This paper proposes a new dynamical system derived from the Chen system. It is designed by replacing the linear term (y-x) in the a equation of the Chen system, by the nonlinear term sinh(y-x). Three cross-sections of the three-dimensional parameter-space of this new system, also called parameter planes, are used in order to investigate numerically the influence of replacing on solutions. It is shown that most of the chaotic solutions in parameter planes of the Chen system are suppressed by replacing, giving rise to periodic solutions. Also, it is shown that most of the unbounded solutions become periodic solutions.